Mutations in TIMM50 cause severe mitochondrial dysfunction by targeting key aspects of mitochondrial physiology. Issue 10 (17th May 2019) - Tort, Frederic; Ugarteburu, Olatz; Texidó, Laura; Gea‐Sorlí, Sabrina; García‐Villoria, Judit; Ferrer‐Cortès, Xènia; Arias, Ángela; Matalonga, Leslie; Gort, Laura; Ferrer, Isidre; Guitart‐Mampel, Mariona; Garrabou, Glòria; et al.
Abstract: 3‐Methylglutaconic aciduria (3‐MGA‐uria) syndromes comprise a heterogeneous group of diseases associated with mitochondrial membrane defects. Whole‐exome sequencing identified compound heterozygous mutations in TIMM50 (c.[341 G>A];[805 G>A]) in a boy with West syndrome, optic atrophy, neutropenia, cardiomyopathy, Leigh syndrome, and persistent 3‐MGA‐uria. A comprehensive analysis of the mitochondrial function was performed in fibroblasts of the patient to elucidate the molecular basis of the disease. TIMM50 protein was severely reduced in the patient fibroblasts, regardless of the normal mRNA levels, suggesting that the mutated residues might be important for TIMM50 protein stability. Severe morphological defects and ultrastructural abnormalities with aberrant mitochondrial cristae organization in muscle and fibroblasts were found. The levels of fully assembled OXPHOS complexes and supercomplexes were strongly reduced in fibroblasts from this patient. High‐resolution respirometry demonstrated a significant reduction of the maximum respiratory capacity. A TIMM50‐deficient HEK293T cell line that we generated using CRISPR/Cas9 mimicked the respiratory defect observed in the patient fibroblasts; notably, this defect was rescued by transfection with a plasmid encoding the TIMM50 wild‐type protein. In summary, we demonstrated that TIMM50 deficiency causes a severe mitochondrial dysfunction by targeting key aspects of mitochondrial physiology, such as the maintenance of proper mitochondrial morphology, OXPHOS assembly, and mitochondrial respiratory capacity. Abstract : TIMM50 deficiency targets key aspects of mitochondrial physiology, such as the maintenance of mitochondrial morphology, OXPHOS complexes and supercomplexes assembly, and mitochondrial respiratory capacity.